2018
DOI: 10.1097/md.0000000000010226
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative platelet-albumin–bilirubin grades predict the prognosis of patients with hepatitis B virus-related hepatocellular carcinoma after liver resection

Abstract: Minimal information is available concerning platelet-albumin–bilirubin (PALBI) grades in patients with hepatocellular carcinoma (HCC) following liver resection. This study aimed to investigate the predictive ability of PALBI grades in patients with a Child–Pugh class A score and hepatitis B virus-related (HBV-related) HCC after liver resection.The data of patients with HBV-related HCC who underwent liver resection from 2010 to 2017 at our center were reviewed (n = 785). Cox regression was used to determine fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In the present study, except for the FIB-4 index, we also showed that DM, liver cirrhosis, tumor size, histology stage, and vascular invasion were important predictors for HCC recurrence; in addition, DM, AFP, and histology stage were independent risk factors for overall survival. It was consistent with the results from the previous studies in which patient factors (DM) [32], liver background factor (liver cirrhosis) [33], and tumor factor (vascular invasion, histology stage, and AFP) [34] determined the outcomes of HCC patients.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, except for the FIB-4 index, we also showed that DM, liver cirrhosis, tumor size, histology stage, and vascular invasion were important predictors for HCC recurrence; in addition, DM, AFP, and histology stage were independent risk factors for overall survival. It was consistent with the results from the previous studies in which patient factors (DM) [32], liver background factor (liver cirrhosis) [33], and tumor factor (vascular invasion, histology stage, and AFP) [34] determined the outcomes of HCC patients.…”
Section: Discussionsupporting
confidence: 91%
“…In daily practice, these may include idiopathic or drug-induced thrombocytopenia, Helicobacter pylori infection, and iron deficiency anemia, all of which are frequently observed. In patients unaffected by such diseases, platelet-ALBI grade, which was recently introduced for patients with HCC and incorporates platelet count into the ALBI score, 26,27 may be used instead. It is possible that combining platelet count with ALBI measurement would allow more accurate determination of fibrosis stage in patients with chronic hepatitis, although this requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-albumin-bilirubin (PALBI), is also widely used to assess liver function and prognosis in HCC. [7][8][9][10][11] However, the role of platelets in HCC is quite complicated and is even conflicting. On the one hand, preoperative thrombocytopenia (platelet count (PLT) <100×10⁹/L) is a significant predictor of poor survival and high risk of recurrence in HCC.…”
Section: Introductionmentioning
confidence: 99%